Liposomal Lactoferrin Exerts Antiviral Activity against HCoV-229E and SARS-CoV-2 Pseudoviruses In Vitro - Sabina Andreu; Inés Ripa; Raquel Bello-Morales; José Antonio López-Guerrero (Viruses, 2023)
A limited number of effective therapies are currently available to treat human coronavirus SARS-CoV-2 and other human coronaviruses, which are responsible for nearly a third of global cases of the common cold. The possibility of new emerging coronaviruses demands powerful new antiviral strategies. Lactoferrin is a well-known protein that possesses anti-inflammatory and immunomodulatory activities, and it has previously shown antiviral activity against several viruses, including SARS-CoV-2. To increase this antiviral activity, here we present bovine liposomal lactoferrin. Liposomal encapsulation of the compound was proven to increase permeability, bioavailability, and time release. In the present work, we compare the antiviral activity of free and liposomal bovine lactoferrin against HCoV229E and SARS-CoV-2 in vitro and in human primary bronchial epithelial cells, and we demonstrated that the liposomal form exerts a more potent antiviral activity than its free form at non-cytotoxic doses.